A case report of glecaprevir/pibrentasvir-induced severe hyperbilirubinemia in a patient with compensated liver cirrhosis. Issue 39 (September 2019) - Yoon, Jae Hyun; Kim, Sun Min; Kang, Gaeun; Kim, Hee Joon; Jun, Chung Hwan; Choi, Sung Kyu
Abstract: Rationale: Glecaprevir/pibrentasvir, a pan-genotypic and ribavirin-free direct acting antiviral agent regimen, has shown significant efficacy and very few serious complications. However, as the drug metabolizes in the liver, it is not recommended in patients with decompensated liver cirrhosis. Herein, we report the case of a patient with compensated liver cirrhosis who developed severe jaundice after glecaprevir/pibrentasvir medication. Patient concerns: A 77-year-old man diagnosed with chronic hepatitis C-related compensated liver cirrhosis visited hospital due to severe jaundice after 12 weeks of glecaprevir/pibrentasvir medication. Diagnoses: On the laboratory work-up, the total/direct bilirubin level was markedly elevated to 21.56/11.68 from 1.81 mg/dL; the alanine aminotransferase and aspartate aminotransferase levels were within the normal range. We checked the plasma drug concentration level of glecaprevir, and 18, 500 ng/mL was detected, which was more than 15 times higher than the drug concentration level verified in normal healthy adults. Interventions: Glecaprevir/pibrentasvir was abruptly stopped and after 6 days, the drug concentration level decreased to 35 ng/mL and the serum total/direct bilirubin decreased to 7.49/4.06 mg/dL. Outcomes: Three months after drug cessation, the serum total bilirubin level normalized to 1.21 mg/dL and HCV RNA was not detected. Lessons: We report what is likely the first known case of severe jaundice after medication with glecaprevir/pibrentasvir in a patient with compensated liver cirrhosis. Clinicians should bear potential hyperbilirubinemia in mind when treating chronic hepatitis C with this regimen and should monitor the patient closely during follow-up laboratory exams, especially in elderly cirrhotic patients.